The Experience of the Charitable Project “Classical Fairy Play” Implementation as an Innovative Form of Management in the Field of Culture - Postupna, Olena; Yeromina , Olena (Theory and Practice of Public Administration, 2019)
The article summarizes the experience of the charitable project “Classical Fairy Play” implementation which has been held annually in Kharkiv, starting from 2012. Within the framework of this project, concerts are held annually on the stage of the Kharkiv M.V. Lysenko National Academic Opera and Ballet Theater with the participation of the actors of the Kharkiv regional municipal enterprise “Youth Academic Symphony Orchestra “Slobozhansky” and world classical music stars for the purpose of raising funds for the needs of health care institutions, educational institutions for children with disabilities and individuals who need charitable help. In particular, in 2012, a free concert was organized for the children of Lubotin specialized boarding school “Dyvosvit” and also sweets were handed out. In 2013 and 2014 testing systems for screening of donor blood for viruses, 12 devices for cleaning and disinfection of air, and medicine for the treatment of young patients with cancer were purchased for the municipal healthcare facility of the Regional Children’s Clinical Hospital No.1. In 2015, a charity concert was held in two cities of Ukraine – Kharkiv and Lviv. The collected funds allowed to purchase high-tech consumables for heart surgery, an air compressor with a set of replaceable filters for the V. Zaitsev State Institution “Institute of General and Emergency Surgery” of National Academy of Medical Sciences of Ukrainein Kharkiv and for the Lviv Regional Clinical Hospital. In 2016 a modern electroneuromyographwas purchased for the Municipal Nonprofit Enterprise of the Kharkiv Regional Council “Regional Children’s Clinical Hospital”. In 2017, for the Municipal Non-profit Enterprise of the Kharkiv Regional Council “V. Shapoval Regional Medical Clinical Urology and Nephrology Center” (Kharkiv) an artificial lung ventilation apparatus “Malyatko” for operated children from 3 to 6 years was purchased. In 2018, the aid was received by the Municipal enterprise of the Kharkiv Regional Council “V.G. Korolenko Special Educational Complex”. The received funds were spent to purchase the Braille printer and tactile graphics printer. In total, for the 7 years of the “Classic Fairy Play” project, 857.7 UAH have been collected, while 878.5 UAH have been expended. Almost every year there is a little more money spenton charity is than risen. This happens at the expense of those institutions, organizations, firms, enterprises, civil society organizations, individual.